2004
DOI: 10.1179/174227104225019490
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Microbubble Contrast-Enhanced Ultrasound Characteristics of Multiple Biliary Hamartomas (von Meyenberg Complexes)

Abstract: Multiple biliary hamartomas (von Meyenberg complexes) are an uncommon benign biliary neoplasm detected incidentally on imaging. To our knowledge the appearances of multiple biliary hamartomas on microbubble contrast-enhanced ultrasound have not been previously described. We report a case using Coherent Contrast Imaging® and Agent Detection Imaging® techniques with the contrast agents Sonovue®and Levovist®. While both methodologies failed to differentiate these focal liver lesions from malignant neoplasms, they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…Sonographic appearances of VMC are varied, being described as multiple hypoechoic lesions,[24] hyperechoic lesions[5] and also a mixture of both hypo- and hyper-echoic lesions. [3] It has been postulated that lesional reflectivity may be dependent on the size and number of the dilated bile ducts and degree of fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sonographic appearances of VMC are varied, being described as multiple hypoechoic lesions,[24] hyperechoic lesions[5] and also a mixture of both hypo- and hyper-echoic lesions. [3] It has been postulated that lesional reflectivity may be dependent on the size and number of the dilated bile ducts and degree of fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…CEUS of two cases of VMC have been described. Berry et al .,[4] reported a case of multiple VMCs that did not demonstrate contrast enhancement in all phases; exclusion of hypovascular metastases was not possible. Hohmann et al .,[7] highlighted the presence of enhancement in a biliary hamartoma on CEUS with ‘washout’ in the delayed phase.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple biliary hamartomas (von Meyenberg complexes) are an uncommon benign biliary neoplasm often detected incidentally on imaging [19]. Typically, multiple biliary hamartomas can mimic metastatic disease.…”
Section: Biliary Hamartomasmentioning
confidence: 99%
“…5. Few case studies exist regarding the CEUS characteristics of biliary hamartoma, and there seem to be contradictory reports regarding the portal and late venous phases [17,22,23]. The diagnostic values of CEUS in our study were calculated on a lesion by lesion basis and therefore cannot be directly transferred to a patientby-patient basis in clinical practice.…”
mentioning
confidence: 83%
“…The interpretation method of CEUS, which is often performed at the bedside, makes fast and accurate diagnoses possible, so that patients with benign FLLs can be excluded, avoiding unnecessary and demanding ionizing radiological follow-up, biopsy, and consequent complications. Previous studies have shown that CEUS may have a high diagnostic value in differentiating FLLs [7,9,10,[17][18][19]. In a recently published study, CEUS showed a high diagnostic accuracy in CTundetermined FLLs [20].…”
mentioning
confidence: 91%